THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION ON BRAND SWITCHING WITH BRAND IMAGE AS A MEDIATING VARIABLE: EVIDENCE FROM ORAL CARE PRODUCT USERS IN KUNINGAN REGENCY, INDONESIA - Tifa Sufiati Istiqomah; Micki Watulandi; Wachjuni; Wildan Agista (Universitas Kuningan, 2026)
This study investigates the influence of product quality and promotion on brand switching, with brand image as a mediating variable, among Pepsodent toothbrush users in Kuningan Regency, Indonesia. Using a quantitative, descriptive-survey approach, data were collected from 190 respondents selected through purposive sampling. Structural Equation Modeling (SEM) with AMOS 23 was employed for analysis. Results reveal that both product quality (CR= 4.581, p < 0.001) and promotion (CR = 2.106, p = 0.035) exert significant positive effects on brand switching. Additionally, product quality (CR = 5.408) and promotion (CR = 3.034) positively influence brand image, which in turn significantly affects brand switching (CR = 1.984, p = 0.047). However, brand image fails to serve as a strong mediator between product quality or promotion and brand switching, as direct effects outweigh indirect effects. These findings suggest that consumers in competitive FMCG markets are more directly driven by perceived product quality and promotional stimuli when making brand-switching decisions, rather than being influenced through the brand image pathway.